Some Associations of Primary Headache Disorders in Mongolia: A Nationwide Population-Based Study - Tsenddorj, Byambasuren; Baldorj, Dorjkhand; Purev, Delgermaa; Enkhtuya, Selenge; Lkhagvaa, Undram; Badrakh, Burmaajav; Luvsannorov, Otgonbayar (Central Asian Journal of Medical Sciences, 2019)
Objective: Headache disorders are the most prevalent public-health problem, affecting people in all countries. Epidemiological data on headaches are not available in Mongolia. Our study aimed to estimate the prevalence of each headache disorders of public health importance and examine their socio-demographic associations, in urban and rural areas. Methods: There were 2,043 biologically unrelated adults (aged 18–65 years) in a door to door survey randomly sampled from Ulaanbaatar (capital of Mongolia) and four aimags (rural), and interviewed by trained researchers using a pilot-tested, validated, structured questionnaire. ICHD-II diagnostic criteria were applied. Results: The observed prevalence of any headache was 66.1%, with a female preponderance of 2:1. The age-standardized prevalence of migraines was 24.2%; prevalence was higher among females than males (OR 2.4, 95% CI 1.9; 2.9, p = .0001), and among those with high education (OR 3.0, 95% CI 1.5; 5.8, p = .002). The age-standardized prevalence of tension-type headache was 29.0%, higher among younger people. The estimated prevalence of all headaches on ≥15 days/month was 11.2% (that of probable medication-overuse headaches was about 70%). Conclusion: The prevalence of primary headaches was 63.9%, with migraines being 24.2%, and tension-type headaches 29.0%. Female gender, higher education level, and family history were associated risk factors for primary headaches. There was a relatively high prevalence of headaches on ≥15 days/month and those with probable medication overuse headaches.